Optimal Income Taxation - 2024; Kaplow, Louis (Journal of Economic Literature, 2024)
This article explores subjects in optimal income taxation characterized by recent research interest, practical importance in light of concerns about inequality, potential for misunderstanding, and prospects for advancement. Throughout the analysis, paths for further investigation are highlighted. Areas of focus include multidimensional abilities and endogenous wages; asymmetric information and the income of founders; production and consumption externalities from labor effort; market power and rents; behavioral phenomena relating to perceptions of the income tax schedule, myopic labor supply, and the interactions of savings, savings policies, and labor supply; optimal income transfers; the relationship between optimal income taxation and the use of other instruments; and issues relating to the social welfare function and utility functions, including non-welfarist objectives, welfare weights, heterogeneous preferences, and taxation of the family.
Keywords: Optimal Taxation; Equity; Inheritance and Gift Taxes; Micro-Based Behavioral Economics; National Government Expenditures; Personal Income